Vrjednovanje i srodni nazivi u hrvatskome jeziku: procjenjivanje, ispitivanje i provjeravanje - Jelaska, Zrinka (2009)
The article discusses different terms concerning the area of language assessment and evaluation. It analyses their similarities and meaning differences.
Projekt MZOS
HRV